SISTEM ADMINISTRASI PADA RUMAH SAKIT STUDI KASUS : RUMAH SAKIT TINGKAT III KABUPATEN KUBU RAYA - Eva Meilinda (Universitas Bina Sarana Informatika, 2013)
In the field of health care, information is needed to improve the quality of health care given optimal health care is not just limited to the treatment technique but also how a hospital, health institution or clinic serving the administration of outpatient and inpatient. Level III Hospital District. Kubu Raya or better known as TK III Rumkit this is one of the hospitals owned by the military who are in the midst of society. In addition to serving the military, civil servants and their families, kindergarten Rumkit III also serve the general society. In the services, especially in the field of administration or record data in the search for new and old patients still running manually, by writing or collecting patient card containing patient data and patient care data that have. In a study conducted by the author, the manual way is applied to Rumkit TK III is not very effective and efficient. Mencarian of data can take a long time and hilangkannya patient data into the problems often faced by the administration.Key words: Hospital Administration System, Administrative Information Systems